Problems of Digitization and Use of Digitized Works by Museums from the Position of German and Ukrainian Copyright Law - ROZGHON, O.; DAVYDOVA, I.; OLIUKHA, V.; SHEPELIUK, V. (Science and Innovation, 2024)
Introduction. The developing trends in the digitization of museum collections encourage the creation of virtual exhibitions. Problem Statement. The laws of Ukraine and Germany have diff erent approaches to understanding a photographic work and non-original photographs reproduced in digital form, and there is a need to systematize and streamline the criteria for the originality of photographic works. Purpose. The purpose of this research is to study the legal nature of the category of "originality", to analyze the criteria that determine the originality of photographic works, to substantiate the potential for legal protection of photographic works of art in digital form, to determine the possibilities of reproduction (digitization) of museum collections and provision of access to them by museums. Material and Methods. A set of general scientifi c and special methods has been used. The materials for the study are publications of domestic and foreign researchers and scholars, norms of the applicable legislation of Ukraine and Germany. Results. The comparative analysis of the doctrine and practice of Ukraine and Germany has led to the conclusion that “originality” is a condition for the protection of works under copyright, according to which it diff ers from other works and is endowed with such features as uniqueness, obscurity, and inimitability. The authors have studied the factors that determine the originality of photographic work: one’s creative contribution; it does neither repeats any already known photographic work nor is a copy of other photographic work; contains a unique composition, angle, method of fi xation, etc. Conclusions. The critical analysis of museum activities has made it possible to identify opportunities for reproducing (digitizing) works of art, providing digital services (free and paid) for access to digitized works, and restrictions (copyright compliance) that arise in museum activities in communication with authors of works of art.